The tourist quest for the “authentic” and the “sacred”: interpretative trails to York Minster - Vecchio, Marta (2011)
This paper is dedicated to the appraisal of visitors’ interpretations of “sacred places” (Shackley, 2001), through the development of a quantitative research dedicated to the cathedral of York. This phenomenon is regarded as paradigmatic for the quest for authenticity through “experiences of signs”, pursued by 21st century tourists (Culler, 1988). It would be argued that most visitors to these sites consider them as different from any other attraction, independently from their faith. This statement would be discussed in the perspective of the postmodern sensibility (Trilling, 1972), analysing the concept of authenticity and the role of religion in the contemporary society, evaluating the tourists’ experiences in “sacred places”, through the concepts of “heterotopia”, “geopiety” and “theoplacity” (Shackley, 2002; Wright, 1966; Belhassen et al., 2008). Thus, the case study about York Minster would be introduced by an evaluation of the site actual tourism management and of its visitors’ profile, then the research methodology would be thoroughly described. The objective of the project would consist in demonstrating the absence of a correlation between the behaviours of tourists inside the cathedral and their opinions about the site, with their religion and the intensity of their religiosity. Opinions specifically would be regarded as the interpretations of the Minster either as a monument or as a worshipping place. This survey would be realised through the administration of 120 questionnaires to the church visitors, analysing the collected data with both descriptive and inferential statics in order to assess the existence and strength of the assumed correlations. The evaluation of the findings would demonstrate solely limitedly the validity of the proposed thesis, providing interesting insights for the tourism management of the cathedral and for the development of future researches in this area.